The Effect of Service Quality on Passenger Satisfaction at PT Titisan Sang Pangeran (Tispa) - Yessie Aryanty; Aslamia Rosa; Zakaria Wahab; Marlina Widiyanti (Publikasi Indonesia, 2024)
This study aims to analyze the influence of service quality on passenger satisfaction at PT Titisan Sang Pangeran (Tispa). The background of this research is based on the importance of quality services in the transportation industry to maintain customer satisfaction and compete in a competitive market. This study uses a quantitative method with the distribution of questionnaires to 300 Tispa passengers during 2023. The sampling method uses purposive sampling, where passengers who use Tispa services during the year are selected as respondents. The results showed that service quality had a positive and significant influence on passenger satisfaction with a correlation coefficient of 0.734 and an R Square of 0.588. This shows that 58.8% of the variation in passenger satisfaction can be explained by the quality of service provided. The factors that most affect passenger satisfaction include vehicle facilities, service responsiveness, and employee friendliness. The conclusion of this study is that improving service quality can significantly increase passenger satisfaction at PT Titisan Sang Pangeran